2020
DOI: 10.1038/s41598-019-57161-9
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic response of the Arabidopsis root metabolome to auxin and ethylene is not predicted by changes in the transcriptome

Abstract: While the effects of phytohormones on plant gene expression have been well characterized, comparatively little is known about how hormones influence metabolite profiles. This study examined the effects of elevated auxin and ethylene on the metabolome of Arabidopsis roots using a highresolution 24 h time course, conducted in parallel to time-matched transcriptomic analyses. Mass spectrometry using orthogonal UPLC separation strategies (reversed phase and HILIC) in both positive and negative ionization modes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Thus EIN2-C provides both transcriptional and translational control to regulate EIN3 and the related EIL1 transcription factor to cause most ethylene responses. This is supported by a recent study where ethylene-stimulated changes in the metabolome did not always correlate with changes in the transcriptome (138). The exception to this model is that short-term, transient responses occur independently of these transcription factors, yet require EIN2 (101).…”
Section: Ethylene Signaling Components and The Canonical Pathwaymentioning
confidence: 60%
See 1 more Smart Citation
“…Thus EIN2-C provides both transcriptional and translational control to regulate EIN3 and the related EIL1 transcription factor to cause most ethylene responses. This is supported by a recent study where ethylene-stimulated changes in the metabolome did not always correlate with changes in the transcriptome (138). The exception to this model is that short-term, transient responses occur independently of these transcription factors, yet require EIN2 (101).…”
Section: Ethylene Signaling Components and The Canonical Pathwaymentioning
confidence: 60%
“…Additionally, research has identified specific histone acetylation marks that are important in ethyleneregulated gene expression by EIN3 (145)(146)(147). Even though more details about transcriptional regulation are being discovered, it is also clear from a recent metabolome study that changes in metabolism occur in response to ethylene that are not predicted by changes in the transcriptome (138). This indicates that there is additional regulation for responses to this hormone.…”
Section: Ethylene Signaling Components and The Canonical Pathwaymentioning
confidence: 99%
“…For examples, integrative metabolomics and proteomics revealed the intricate balance between JA and SA in the MAP kinase (MPK) 4-mediated plant immune response [153]. Increases of both auxin and ethylene caused changes in phenylpropanoid, glucosinolate, and fatty acid metabolism in Arabidopsis root metabolome, and the changes correlated negatively with the corresponding transcriptome data [154], indicating post-transcriptional events such as changes in enzyme activity and/or transport processes played a role in the metabolomic changes. Stomatal guard cells have been used as a model system for studying hormone function and crosstalk.…”
Section: Metabolomics Of Hormonal Crosstalkmentioning
confidence: 99%
“…In a comprehensive analysis of metabolome and transcriptome of Arabidopsis thaliana over-expressing a MYB transcription factor, novel genes involved in flavonoid biosynthesis and novel anthocyanins were identified. Nevertheless, given the post-transcriptional modification and other levels of regulation, the dynamic response of the Arabidopsis metabolome to various factors may not be predicted by transcriptome changes ( Hildreth et al, 2020 ). The clues of regulatory mechanisms in Dichocarpum could also be identified by the integration of non-targeted metabolomics and full-length transcriptomics to gain a more objective understanding of the association between genes and specialized metabolites.…”
Section: Introductionmentioning
confidence: 99%